Electroacupuncture ameliorates inflammatory response induced by retinal ischemia-reperfusion injury and protects the retina through the DOR-BDNF/Trkb pathway - Guo, Runjie; Zhang, Yongjie; Geng, Yue; Chen, Ping; Fu, Tiantian; Xia, Yong; Zhang, Ren; Zhu, Yuan; Jin, Jingling; Jin, Nange; Xu, Hong; Tian, Xuesong (Frontiers in Neuroanatomy, 2023)
Objectives: Retinal ischemia-reperfusion injury (RIRI) is the common pathological basis of many ophthalmic diseases in the later stages, and inflammation is the primary damage mechanism of RIRI. Our study aimed to assess whether electroacupuncture (EA) has a protective effect against RIRI and to elucidate its related mechanisms. Methods: A high-intraocular pressure (HIOP) model was used to simulate RIRI in Wistar rats. EA was applied to the EA1 group [Jingming (BL1) + Shuigou (GV26)] and the EA2 group [Jingming (BL1) + Hegu (LI4)] respectively for 30 min starting immediately after the onset of reperfusion and repeated (30 min/time) at 12 h and then every 24 h until days 7 after reperfusion. The pathological changes in the retina were observed by H and E staining after HIOP. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining was utilized to observe retinal cell apoptosis. The mRNA expression of IL1-β, TNF-α, IL-4, IL-10, δ-opioid receptor (DOR), brain-derived neurotrophic factor (BDNF), and tropomyosin-related kinase B (TrkB) in the retina was measured by quantitative real-time PCR. Results: HIOP caused structural disorders of the retina, decreased RGCs, and increased retinal cell apoptosis. At 1 and 3 days of RIRI, retinal apoptotic cells in the EA group were significantly reduced, while there was no distinct difference in the EA group compared with the HIOP group at 7 days of RIRI. Compared with that in the HIOP group, the expression of anti-inflammatory factors, DOR and TrkB was increased, and the expression of pro-inflammatory factors was decreased in the EA group. In contrast, HIOP had no appreciable effect on BDNF expression. Conclusion: EA at Jingming (BL1) and Shuigou (GV26) or at Jingming (BL1) and Hegu (LI4) may inhibit RIRI induced inflammation through activating the DOR-BDNF/TrkB pathway to protect the retina, especially the pair of Jingming (BL1) and Shuigou (GV26) has better inhibitory effects on inflammation.